The social construction of tiwala and the dynamics of social networks in a Filipino rural poor community by Lily V. Mangubat. - Mangubat, Lily V (2008)
This study explored tiwala (roughly translated as trust) as a Filipino construct--its meaning among resource persons in a rural poor community, its nuanced interpretation in situations where people have limited access to resources, as well as its relationship to the creation of social networks for managing or changing their existing realities. Taking a social constructionist position, the research privileged the local milieu -- how people interpret their realities, what becomes meaningful to them in their interaction with others, and how they manage uncertainties in their lives and social encounters. It involved immersion in the activities of the community, informal interviews, and group discussions. Towards the end of the field research, the findings were validated with some key informants to ensure that they captured their representations of tiwala. As the findings show, tiwala appears to be a mechanism that provides some semblance of stability and predictability in a precarious world. It provides some semblance of stability and predictability in a precarious world. It provides a symbol of dependability and is associated with social support systems which help people cope with the difficulties of daily living. The levels of tiwala identified by informants reveal its ontersubjective nature. Tiwala-whether it is tiwala sa sarili (trust in one's self), tiwala ng kapwa (trust of others) and tiwala sa kapwa (trust in others), or tiwala sa samahan (trust in organizations)-is developed or eroded in the process of social interaction and based in the socially constructed knowledge about the self and others. However tiwala sa samhan does not automatically ensue, regardless of the kinship ties and close interpersonal relations among several members.